Detection rate and characteristics of heart failure, depending on the diagnostic criteria in COVID-19 survivors one year after hospitalization - Yu. V. Mareev; M. M. Lukyanov; S. Yu. Martsevich; A. A. Pulin; N. P. Kutishenko; E. Yu. Andreenko; V. P. Voronina; V. A. Dindikova; N. A. Dmitrieva; A. N. Makoveeva; O. V. Lerman; E. Yu. Okshina; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To estimate the detection rate of heart failure (HF), using various diagnosis criteria, among patients aftr 12 months after hospital treatment for coronavirus disease 2019 (COVID-19).Material and methods. The study included 185 patients from the TARGET-VIP registry who came for a visit 12 months after hospitalization for COVID-19. To identify HF with reduced (HFrEF) and mildly reduced (HFmrEF) ejection fraction (EF), the European Society of Cardiology (ESC) criteria (2016 and 2021) were used. To identify HF with preserved EF (HFpEF), we used the ESC criteria (2016 and 2021), as well as the 2018 Russian guidelines and H2FPEF score.Results. In the analyzed group, there were no patients with EF <40%, while one patient had EF of 48% and 184 patients — ≥50%. The patient with EF of 48% was not diagnosed with HF due to the absence of HF signs and symptoms. The presence of HFpEF was confirmed in 31,4% of patients according to 2018 Russian criteria and 2021 ESC criteria (first version of the diagnosis), in 12,5% according to the 2016 ESC criteria, 11% according to ESC 2021 criteria (second version of the diagnosis) and in 2,2% on the H2FPEF score. The proportion of HF diagnosed for the first time according to the 2016 ESC criteria was 78% of the total number of HF cases.Conclusion. Among the examined patients 12 months after hospital treatment for COVID-19, there were no cases of HFrEF and HFmrEF. The proportion of HFpEF cases, depending on the diagnostic criteria used, varied significantly from 2,2 to 31,4%. The previously established diagnosis of HF was confirmed in 83% of cases at a visit 12 months after discharge from the hospital. Using the 2016 ESC criteria and the corresponding 2020 Russian Society of Cardiology guidelines, the proportion of newly diagnosed HF was 78% of all patients.